2008
DOI: 10.1177/039463200802100306
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Porcine Orexin a on Glucagon Plasma Concentrations in Pigs

Abstract: In 1998, Orexin A was added to the long list of orexigenic neuropeptides of the brain's physiology. Orexin A is involved in the central control of appetite and in energy homeostasis, as well as in the regulation of many other physiological functions. It is produced by a small cluster of the brain's neurons, located mainly in and around the lateral hypothalamic area. This site is known to be involved in regulating feeding in mammals. An intracerebroventricular injection of Orexin A into the rat's brain causes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
1
1
0
Order By: Relevance
“…Together, these data suggest that the tonic action of orexins on arcuate NPY neurons might lead to increased glucagon secretion and reduced liver glycogen. In agreement with such an idea, previous studies have shown that icv injection of either NPY or orexin-A increases circulating glucagon levels (40,41). However, additional experiments are needed to fully prove this hypothesis.…”
Section: Discussionsupporting
confidence: 57%
“…Together, these data suggest that the tonic action of orexins on arcuate NPY neurons might lead to increased glucagon secretion and reduced liver glycogen. In agreement with such an idea, previous studies have shown that icv injection of either NPY or orexin-A increases circulating glucagon levels (40,41). However, additional experiments are needed to fully prove this hypothesis.…”
Section: Discussionsupporting
confidence: 57%
“…This phase is generally considered as a direct consequence of the effects of mediators released from mast cells activated during the early reaction. Inflammatory and allergic diseases are mainly orchestrated by antigen-specific CD4+ T cells, eosinophils and mast cells (55). Prostanoids are one of the arachidonic metabolites, which are produced by a variety of inflammatory cells upon stimulation and are thought to be involved in the pathogenesis of diseases as well as the regulation of homeostasis.…”
mentioning
confidence: 99%